Heat transfer enhancement in a supercritical CO2–water printed circuit heat exchanger using rectangular cavities and pulsating flow - Shiyu Lai; Tieyu Gao; Xiangrui Meng; Liang Zhou; Zhihui Zhang; Ruihao Cheng (AIP Advances)
The printed circuit heat exchanger (PCHE) significantly reduces thermodynamic load and footprint in the heat exchange process of the supercritical carbon dioxide Brayton cycle. This study aims to investigate the efficiency of pulsation technology in augmented heat transfer within cavities and to optimize the key variables of the pulsating flow in the hot-side by evaluating the response of the micro-channels. Results indicate that the cavity structures exhibit improved thermal-hydraulic characteristics, reducing water-side flow resistance by 4.6%. Pulsating flow can additionally strengthen thermal exchange at low Reynolds numbers. The enhanced thermal performance stems from pulsating flow-induced periodic vortices, generating intense fluid disturbances within the micro-channel. These organized vortex structures substantially boost local turbulent kinetic energy, disrupt the thermal boundary layer, effectively reduce thermal resistance, and improve field synergy. Across the studied pulsating frequencies (10–35 Hz) and amplitudes (0.1–1.1), heat transfer enhancement and power consumption demonstrate strong dependencies on these parameters. Compared to traditional straight channels, changes in frequency and amplitude can improve the effectiveness of PCHE by 7.4% and 11.1%, respectively, with the maximum comprehensive performance index on the hot-side reaching ∼1.40 and 1.52.